Giftedness and peer group: an exploration of the representational repertory on giftedness in the early school age - Baccassino, Francesca; Pinnelli, Stefania (Universitas Majalengka, 2022)
There has been growing interest in the issue of giftedness and in educational paths which can counteract the development of misrepresentations and negative attitudes on the theme. These forms of common sense contribute to interpreting social reality using shortcuts in thinking that are sometimes inadequate to explain the complexity of human personality and that, therefore, may generate some stereotypes and prejudices. The analysis and orientation of distorted representations could prompt the activation of inclusive behaviour towards gifted peers. This contribution therefore focuses on the representations concerning giftedness in the peer group. The project, carried out with pupils of primary school class, aims to explore the representations and attitudes of children exposed to a path of awareness on giftedness in order to support a correct and inclusive representation of the phenomenon.